Building support for children and families affected by stroke (BUILD CARE): Study protocol - Maja Kevdzija; Lisa Bartha-Doering; Ruth Heying; Ann Heylighen; Andrea Jelić; Pleuntje Jellema; Anna Franziska Kalhorn; Sophie Mandl; Gesine Marquardt; Birgit Moser; Magdalena Muszynska-Spielauer; Els Ortibus; et al. (PLoS ONE, 2025)
Childhood stroke is a rare condition that significantly impacts affected children and their families due to children’s frequently persisting cognitive, physical, and behavioural problems. Existing research on adult stroke shows that the built environment plays a major role in their (partial or possible) recovery and everyday life, but its role has been overlooked in children population. This multidisciplinary research study aims to investigate (1) the role of informal (i.e., home, neighbourhood, school) and formal (i.e., hospital, rehabilitation clinic, outpatient clinic) care environments in the everyday life of children and families confronted with childhood stroke; (2) the families’ financial burden resulting from this rare disease and their economic situation likely affecting the access to care, informal care provision and ability to carry out home modifications.; as well as (3) children’s stroke-related cognitive impairments affecting their experiences of the built environment and their care. The research consists of the preparatory research phase, where existing materials are explored, and three main research phases, each related to one or multiple project objectives. A multi-method approach is adopted, including qualitative (in-depth interviews and participatory creative methods) and quantitative (online questionnaire and cognitive assessments) research methods. Participants are children affected by stroke and their families in Austria, Belgium and Germany. This is a 3-year project that will continue until the end of August 2025. Ethical approvals in all countries were obtained at the time of protocol submission, and data collection for all three research phases started in the second half of 2023 and is currently ongoing. This project will offer first insights into the role of built (care) environments in the experiences of families affected by childhood stroke. Findings are expected to deliver information on their design to improve the life of children affected by this rare disease and their families.